Mapping the SLP76 interactome in T cells lacking each of the GRB2-family adaptors reveals molecular plasticity of the TCR signaling pathway - Ruminski, Kilian; Celis-Gutierrez, Javier; Jarmuzynski, Nicolas; Maturin, Emilie; Audebert, Stephane; Malissen, Marie; Camoin, Luc; Voisinne, Guillaume; Malissen, Bernard; Roncagalli, Romain (Frontiers in Immunology, 2023)
The propagation of intracellular T cell receptor (TCR) signals involves several adaptor proteins that each assemble multimolecular signaling complexes (signalosomes) coordinating the propagation and diversification of TCR signals. The global characterization of changes in protein-protein interactions (PPI) following genetic perturbations is critical to understand the resulting phenotypes. Here, by combining genome editing techniques in T cells and interactomics studies based on affinity purification coupled to mass spectrometry (AP-MS) analysis, we determined and quantified the molecular reorganization of the SLP76 interactome resulting from the ablation of each of the three GRB2-family adaptors. Our data showed that the absence of GADS or GRB2 induces a major remodeling of the PPI network associated with SLP76 following TCR engagement. Unexpectedly, this PPI network rewiring minimally affects proximal molecular events of the TCR signaling pathway. Nevertheless, during prolonged TCR stimulation, GRB2- and GADS-deficient cells displayed a reduced level of activation and cytokine secretion capacity. Using the canonical SLP76 signalosome, this analysis highlights the plasticity of PPI networks and their reorganization following specific genetic perturbations.